An Efficient & Less Complex Solution to Mitigate Impulsive Noise in Multi-Channel Feed-Forward ANC System with Online Secondary Path Modeling (OSPM) - Ihsan Khan, Fahad; Umer Javed, Muhammad; Kıvanç Türeli, Didem (International Journal of Advanced Engineering, Management and Science, 2023)
This paper deals with impulsive noise (IN) in multichannel (MC) Active Noise Control (ANC) Systems with Online Secondary Path Modelling (OSPM) employing adaptive algorithms for the first time. It compares performance of various existing techniques belonging to varied computational complexity range and proposes four new methods, namely: FxRLS-VSSLMS, VSSLMS-VSSLMS, FxLMAT-VSSLMS and NSS MFxLMAT-VSSLMS to deal with modest to very high impulsive noise (IN). Simulation results show that these proposed methods demonstrated improved performance in terms of fast convergence speed, lowest steady state error, robustness and stability under impulsive environment in addition to modelling accuracy for stationary as well as non-stationary environment besides reducing computational complexity many folds.